2016
DOI: 10.1186/s13223-016-0137-x
|View full text |Cite
|
Sign up to set email alerts
|

Filaggrin gene mutations and new SNPs in asthmatic patients: a cross-sectional study in a Spanish population

Abstract: BackgroundSeveral null-mutations in the FLG gene that produce a decrease or absence of filaggrin in the skin and predispose to atopic dermatitis and ichthyosis vulgaris have been described. The relationship with asthma is less clear and may be due to the influence of atopy in patients with associated asthma.MethodsFour hundred individuals were included, 300 patients diagnosed with asthma divided into two groups according to their phenotype (allergic and non-allergic asthma) and 100 strictly characterized contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…The defects in structural epidermal proteins outlined above collectively contribute to a dysfunctional cutaneous barrier that underlies the AD phenotype of dry, inflamed skin, and also serves as a site for allergic sensitization to antigens. Indeed, FLG mutations have been reported to be associated with atopic asthma, allergic rhinitis, nickel allergy and food allergy, suggesting that FLG mutation‐associated stratum corneum barrier defects lead to increased percutaneous allergen exposure. Apart from in one recent and relatively small study, FLG mutations have not been associated with asthma without AD, and most of the identified asthma‐associated genes are not associated with AD, suggesting that atopic asthma is a distinct subentity .…”
Section: Skin Barrier Dysfunctionmentioning
confidence: 99%
“…The defects in structural epidermal proteins outlined above collectively contribute to a dysfunctional cutaneous barrier that underlies the AD phenotype of dry, inflamed skin, and also serves as a site for allergic sensitization to antigens. Indeed, FLG mutations have been reported to be associated with atopic asthma, allergic rhinitis, nickel allergy and food allergy, suggesting that FLG mutation‐associated stratum corneum barrier defects lead to increased percutaneous allergen exposure. Apart from in one recent and relatively small study, FLG mutations have not been associated with asthma without AD, and most of the identified asthma‐associated genes are not associated with AD, suggesting that atopic asthma is a distinct subentity .…”
Section: Skin Barrier Dysfunctionmentioning
confidence: 99%
“…Filaggrin belongs to the keratin gene family and is involved in the differentiation of epithelial cells (Zhong et al 2005 ). The loss-of-function in mutations of FLG in humans is correlated with airway hyperresponsiveness, a characteristic of PM-related airway disease (Berg et al 2012 ; Cubero et al 2016 ; Palmer et al 2007 ). A systemic review of the literature concerning COX-2 and Filaggrin pointed out that PM downregulates Filaggrin via COX-2 expression/PGE 2 production, leading to skin barrier dysfunction (Lee et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Only 1 study has assessed the prevalence of FLG mutations in a Spanish population, specifically in a cohort of asthma patients and a corresponding control group . That study revealed frequencies of 2% and 1% for R501X and 2282del4, respectively, in the control group, and lower frequencies in the asthma cohort (1% and absent, respectively).…”
Section: Introductionmentioning
confidence: 99%